Diverse NLR immune receptors activate defence via the RPW8‐NLR NRG1. Issue 2 (25th January 2019) - Castel, Baptiste; Ngou, Pok‐Man; Cevik, Volkan; Redkar, Amey; Kim, Dae‐Sung; Yang, Ying; Ding, Pingtao; Jones, Jonathan D. G.
Summary: Most land plant genomes carry genes that encode RPW8‐NLR Resistance (R) proteins. Angiosperms carry two RPW8‐NLR subclasses: ADR1 and NRG1. ADR1s act as 'helper' NLRs for multiple TIR‐ and CC‐NLR R proteins in Arabidopsis. In angiosperm families, NRG1 co‐occurs with TIR‐NLR Resistance ( R ) genes. We tested whether NRG1 is required for signalling of multiple TIR‐NLRs. Using CRISPR mutagenesis, we obtained an nrg1a‐nrg1b double mutant in two Arabidopsis accessions, and an nrg1 mutant in Nicotiana benthamiana . These mutants are compromised in signalling of all TIR‐NLRs tested, including WRR4A, WRR4B, RPP1, RPP2, RPP4 and the pairs RRS1/RPS4, RRS1B/RPS4B, CHS1/SOC3 and CHS3/CSA1. In Arabidopsis, NRG1 is required for the hypersensitive cell death response (HR) and full oomycete resistance, but not for salicylic acid induction or bacterial resistance. By contrast, nrg1 loss of function does not compromise the CC‐NLR R proteins RPS5 and MLA. RPM1 and RPS2 (CC‐NLRs) function is slightly compromised in an nrg1 mutant. Thus, NRG1 is required for full TIR‐NLR function and contributes to the signalling of some CC‐NLRs. Some NRG1‐dependent R proteins also signal partially via the NRG1 sister clade, ADR1. We propose that some NLRs signal via NRG1 only, some via ADR1 only and some via both or neither.